Mental Health Survey On Football Athletes Aged 18 ASIFA (Aji Santoso International Football Academy) - Putra, I Gusti Lanang Agung Rahadian; Rahayuni, Kurniati (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the mental health of aged 18 ASIFA football athletes, Mental health can be interpreted in large or small ways. Mental health is a form of successful adjustment or not to psychopathology, which describes a person who does not have psychological, emotional, behavioral, and mental disorders. Social. The Mental Health Inventory (MHI) has two aspects, namely (1) Psychological Distress (psychological distress) is divided into several parts such as (a) anxiety, (b) depression, (c) loss of emotional control/loss of behavioral control, (2) Psychological well-being is also divided into several parts, including (a) Life satisfaction, (b) Emotional ties, (c) General positive effect. This research uses a descriptive survey method and uses a questionnaire as a data collection tool. 20 athletes filled out questionnaires in this research. In this research data, the athletes who were respondents had varying mental health data results, and were each unique. With the total results from 20 respondents, the following results were obtained: anxiety, 466 points; depression, 476 points; loss of emotional control, 549 points; life satisfaction, 740 points; emotional ties, 661 points; and general positive effect, 419 points.